Analisis performa akademik siswa berdasarkan status sosial ekonomi dalam mata pelajaran Bahasa Indonesia di sekolah dasar - Ulfatul Khasanah; Suci Dwiyana; Zulfa Nur Permadi; Mohammad Edy Nurtamam (Jurnal Pendidikan Dasar, 2025)
Abstract. This study aims to analyze the influence of socioeconomic status on students' academic performance in the Indonesian language subject for sixth-grade students at UPTD SDN Tunjung 1 Bangkalan. The research employs a descriptive qualitative approach, with data collection techniques including interviews, observations, and documentation. The research subjects consist of teachers and students with varying socioeconomic backgrounds. Data validity is ensured through methodological triangulation, while data analysis is conducted through data reduction, data presentation, and conclusion drawing. The results indicate that students from families with higher socioeconomic status have better access to educational facilities such as books, the internet, and additional academic tutoring. This provides them with greater opportunities to achieve higher academic performance. Conversely, students from lower socioeconomic backgrounds often face limitations in accessing adequate learning resources, which affects their motivation and academic outcomes.To address this academic disparity, active involvement from various stakeholders is required. Schools and parents must provide more equitable educational support, while the government should facilitate tutoring programs, additional learning resources, and scholarships for underprivileged students. With the implementation of appropriate strategies, it is expected that all students will have equal learning opportunities and be able to achieve optimal academic outcomes.keywords:  Academic Performance,  Education, Elementary School, Socioeconomic Status.